PERBANDINGAN PEMERIKSAAN TRIGLISERIDA METODE GLYCEROL BLANKING DAN NON GLYCEROL BLANKING PADA SIROSIS HEPATIS - Sri Widyaningsih; Leonita Anniwati; Juli Soemarsono (Indonesian Association of Clinical Pathologist and Medical laboratory, 2012)
Liver cirrhosis is a chronic liver disease with fibrosis and impairment of function. In liver disease increasing endogenous free glycerol has been found which constitutes a source of interference in the measurement of (TG). The aim of this study is to compare the glycerol blanking (TG-GB) which does not interfere with endogenous free glycerol to non glycerol blanking (TG-NGB) method in measuring TG in liver cirrhosis patients. In this study, sera were obtained from 22 liver cirrhosis and 30 healthy persons. All sera were measured for TG using TMS 1024i (Tokyo Boeki Medical System) with glycerol blanking (TG-GB) to non glycerol blanking (TG-NGB) method. In addition to this study, measurement of free glycerol was also compared to difference calculated TG-NGB and TG-GB in liver cirrhosis patients. The mean of TG-GB and TG-NGB measurements from healthy persons was 115.30±70.35 mg/dL and 121.27±67.14 mg/dL (p=0.108), respectively. The mean of TG-GB and TG-NGB measurements from liver cirrhosis patients was 101.09± 78,55 mg/dL and 120.91±79.44 mg/dL (p<0.0001). There was a significant difference between TG-GB and TG-NGB, and there was no significant difference between measurement of free glycerol to difference calculated TG-NGB and TG-GB in liver cirrhosis (p=0.784). However, there was a significant correlation between TG-GB and TG-NGB in healthy persons and liver cirrhosis patients. (p<0.0001). The measurement of TG-GB is more accurate than TG-NGB method in liver cirrhosis patients.